Use of Nearshore and Estuarine Areas of the Southeastern Bering Sea by Gray Whales (Eschrichtius robustus) - Gill, Jr., Robert E.; Hall, John D. (ARCTIC, 1983)
During spring aerial surveys of the coast of the southeastern Bering Sea significant numbers of gray whales were seen in nearshore waters along the north side of the Alaska Peninsula. Many (50-80%) of these animals were observed surfacing with mud trails or lying on their sides, characteristics both associated with feeding. A migration route close to shore (within 1-2 km) was used until whales neared Egegik Bay, where they began to head west 5-8 km offshore, across northern Bristol Bay. Smaller numbers of gray whales were present throughout summer in nearshore waters and estuaries along the north side of the Alaska Peninsula. At Nelson Lagoon gray whales normally used the lagoon in spring, were absent during early summer, returned in mid-summer, and then were present until late November when they departed for the wintering grounds. Gray whales were present in the lagoon most often during periods of peak tidal flow; those that appeared to be feeding were oriented into the current. Three behaviors that appeared to be associated with feeding were observed: side-feeding from a stationary position within shallow waters of lagoon channels, diving within the lagoon and in nearshore waters, and elliptical side-feeding in the surf zone along the outer coast. Large crustaceans of the genus Crangon were available to and probably eaten by gray whales at Nelson Lagoon.Key words: gray whale, Eschrichtius robustus, feeding, behavior, estuaries, Bering Sea, Alaska Mots clés: baleine grise de Californie, Eschrichtius robustus, alimentation, comportement, estuaires, mer de Béring, Alaska